Silicon-Based Arrayed waveguide gratings for WDM and spectroscopic analysis applications. (March 2022) - Zou, Jun; Sun, Fangyuan; Wang, Changhui; Zhang, Ming; Wang, Junnan; Lang, Tingting; Wang, Xuyang; Le, Zichun; He, Jian-Jun
Highlight: The effect of two widely used star couplers on the performance of silicon AWGs is investigated and using the optimized star coupler, ultracompact low resolution AWGs based on single bend per path and S-shaped phase array layouts are demonstrated for CWDM and prefilters applications. High resolution 2  N  × 1 and ( N  + 1) × ( N  + 1) AWG multiplexers, together with a polarization insensitive demultiplexer using ( N  + 1) × ( N  + 1) AWG cascaded with polarization rotator-splitter/ combiner-rotators, are demonstrated for DWDM applications. Sub-nm resolution spectrometers based on bidirectional AWGs with ultracompact size are also demonstrated and compared. All the experimental results indicate that a smaller footprint for the phase region of AWGs contributes to an improved performance in their spectral responses. The approaches of further reducing the footprint of phase region of an AWG are also discussed. Abstract: We compare the performance of silicon-based arrayed waveguide gratings (AWGs) with star couplers of Rowland and Confocal configurations, respectively, for both TE and TM polarizations. The star coupler with Rowland configuration and constant projection period for phased array waveguides on the tangent line at the grating pole shows sufficiently small aberration for all output channels of AWGs, achieving a better spectral performance compared to the Confocal configuration. The spectral performance of AWGs is also highly dependent on phase errors resulting from fabrication imperfections which are unavoidable in current fabrication technology, hence it is of significant importance to make the phase region of AWGs as small as possible. Using the optimized star coupler configuration, ultracompact large channel spacing AWGs employing a single bend with a different radius for each waveguide in the phase array and a S-shaped waveguide array, respectively, are fabricated and compared, together with high resolution (de)multiplexers utilizing the cascade of ( N  + 1) × ( N  + 1) AWGs and polarization combiner-rotator/rotator-splitter. High resolution ultracompact spectrometers using bidirectional ( N  + 1) × ( N  + 1) AWGs operating at TE and TM polarizations are also designed and fabricated. All the experimental results indicate that a smaller footprint for the phase region of AWGs contributes to an improved performance in their spectral responses. We also discuss the ways to reduce the size of phase region and suggest that decreasing the pitch of adjacent output waveguides on the imaging plane is an effective way. This paper provides design considerations for silicon-based AWGs towards various applications such as wavelength division multiplexing (WDM) and spectroscopic analysis.